Examining the Association Between Name Characteristics and Academic Career Success of UK Neurologists - Marianna E. Kapsetaki; Laetisha Witoyo (Names)
This study aimed to examine whether name characteristics of UK neurologists are related to their academic career success. Biographical information and bibliometrics of all UK consultant neurologists (N=1010) were obtained from online sources. Neurologists with a shorter surname and a higher consonant:vowel ratio in their surname had more citations. The surname's complexity was negatively associated with the h-index and citations, and was lower in neurologists currently affiliated with a top university. Top university graduates for their medical degree had fewer syllables in their first and last name. Neurologists with a popular forename had higher bibliometrics, were faster in publishing their first paper, more likely to be top university graduates for their medical degree and more likely to be currently affiliated with a university. Neurologists with a popular surname were more likely to be top university graduates for their medical degree. Male neurologists with more masculine forenames were more likely to be top university graduates, were faster in publishing their first paper, and had higher bibliometrics. This study revealed that there is an association between name characteristics and career success of UK consultant neurologists.